2017
DOI: 10.3390/polym9120734
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of a Polyimide-Coated Ultrafine Gilt Molybdenum Wire and Its Knitted Mesh Used for Electromagnetic Reflectors

Abstract: Abstract:In this work, polyimide (PI) was coated onto an ultrafine gilt molybdenum wire in order to protect the gilt surface and prepare an electrically stable wire mesh material which can be widely used in space. The surface of the PI-coated gilt molybdenum wires was characterized using FTIR, SEM, and EDS. Factors such as temperature stability of the PI coating, mechanical properties of the PI-coated gilt molybdenum wires, contact resistance stability, and electromagnetic microwave reflectivity of the their k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Polyimide (PI) filaments as reinforcements for advanced composites have attracted considerable research attention for their favorable thermal stability, outstanding mechanical properties, excellent chemical and radiation resistance, and special dielectric properties [1,2,3,4,5]. For composites, good interfacial adhesion between fiber and matrix facilitates the load transfer efficiency and improves the strength and toughness of the composite materials [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Polyimide (PI) filaments as reinforcements for advanced composites have attracted considerable research attention for their favorable thermal stability, outstanding mechanical properties, excellent chemical and radiation resistance, and special dielectric properties [1,2,3,4,5]. For composites, good interfacial adhesion between fiber and matrix facilitates the load transfer efficiency and improves the strength and toughness of the composite materials [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Excellent performance of polyimides like highly mechanical and thermally stable, electrical, wide chemical resistance, and relatively low dielectric constants, and so forth makes themselves attractive candidates in microelectronic and aerospace engineering . Over the past years, numerous diamines or dianhydrides are designed aiming to obtain polyimides with ultralow dielectric constant, high glass transition temperature, good biocompatibility, low coefficient of linear expansion, ultrahigh tensile strength, optoelectronic and gas separation properties, and so forth, Nevertheless, most of these polyimides based on aromatic building blocks can easily lead to defects like insolubility and low transmittance and hence impede their molding processing and application in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 34 reported flexible warpknitted metal meshes in terms of the design requirements, materials, and knitting process. Shao et al 35 reported knitted polyimide-coated gilt molybdenum mesh fabrics for antenna applications, which show strong reflectivity for EM microwaves in the S-band. As a consequence, employing warp-knitting technology to link ultra-fine metal wires with micron diameters into flexible mesh-shaped materials has considerable potential for the preparation of excellent EMI shielding materials.…”
mentioning
confidence: 99%